Teacher identity, Islamic behavior, and project-based learning methods for madrasah teachers: A phenomenological approach - Zamsiswaya, Zamsiswaya; Mounadil, Abdelaziz Ibrahim; Abdel-Latief, Sara (LPMPP Universitas Negeri Yogyakarta, 2024)
A project-based learning method is required to develop students' scientific thinking in akidah akhlak (moral theology). This study employed a phenomenological approach to investigate whether and to what extent identity processes and Islamic behavior are developing project-based learning methods for madrasah aliyah teachers of moral theology. It involved twenty moral theology teachers and in-depth interviews to reveal the narrative of teachers' practice in using project-based learning methods. Thematic analysis of twenty teachers' two-group interviews showed that teachers' personal beliefs provided a religiously motivated narrative framework that aided in interpreting one's experiences. Individual Islamic behavior, religiosity, and identity creativity play a role in developing project-based learning methods for moral theology. In addition to attributing creativity from a God-given personality to learning in moral theology, the primary bond in developing project-based learning methods is the application of Islamic principles and Islamic behavior. Following the learning of moral theology, students' identities, Islamic behavior, and scientific thinking, the use of project-based learning methods by madrasah teachers experienced a significant increase in quality. Finally, the findings of this exploratory study indicate that Islamic behavior and personal identity can enhance project-based learning methods. Large-scale research could provide more evidence to reconsider the role of religious education in teacher training as an essential factor in developing project-based learning methods for moral theology teachers.